Sleep quality among non-hospitalized COVID-19 survivors: a national cross-sectional study - Hoang, Huong Thi Xuan; Yeung, Wing Fai; Truong, Quyen Thi Mai; Le, Cuc Thi; Bui, Anh Thi My; Bui, Quang Vinh; Le, Quyen Thi Le; Quach, Linh Ha (Frontiers in Public Health, 2024)
Objectives Insomnia is a common symptom after COVID-19 infection; however, its current evidence was among hospitalized COVID-19 patients. This study aimed to assess the prevalence of insomnia and identify its association with depression and anxiety among non-hospitalized COVID-19 recovered population. Methods We conducted a cross-sectional online survey of 1,056 COVID-19 survivors within 6 months of initial COVID-19 infection and retrieved did not require hospitalization. The Insomnia Severity Index, and Depression Anxiety and Stress Scale-14 were used. Multivariate logistic regression was used to examine the associations between depressive and anxiety score, and participants’ insomnia level. Results The prevalence of insomnia was 76.1%, and among those, 22.8% of participants scored for severe insomnia. One third of participants reported worse sleep quality, shorter sleep duration, and harder to fall asleep, half reported more awaken nights after COVID-19 infection. Participants with depressive (OR 3.45; 95%CI 1.87–6.34) or anxiety (OR 3.93; 95%CI 2.52–6.13) had significantly higher odds of developing insomnia. Other risk factors of insomnia included pre-existing chronic conditions and higher education level, while COVID-19 symptoms and duration were not significantly associated. Conclusion Our study highlights the substantial burden of insomnia among non-hospitalized COVID-19 survivors and the significant association of depression and anxiety on the development of this long-term effect of COVID-19. These findings underscore the need for comprehensive interventions that address both sychological and sleeping health in this population.